Systematic Review and Quality Appraisal of Economic Evaluation Publications in Dentistry. (October 2015) - Tonmukayakul, U.; Calache, H.; Clark, R.; Wasiak, J.; Faggion, C.M.
Economic evaluation (EE) studies have been undertaken in dentistry since the late 20th century because economic data provide additional information to policy makers to develop guidelines and set future direction for oral health services. The objectives of this study were to assess the methodological quality of EEs in oral health. Electronic searching of Ovid MEDLINE, the Cochrane Library, and the NHS Economic Evaluation Database from 1975 to 2013 were undertaken to identify publications that include costs and outcomes in dentistry. Relevant reference lists were also searched for additional studies. Studies were retrieved and reviewed independently for inclusion by 3 authors. Furthermore, to appraise the EE methods, 1 author applied the Drummond 10-item (13-criteria) checklist tool to each study. Of the 114 publications identified, 79 studies were considered full EE and 35 partial. Twenty-eight studies (30%) were published between the years 2011 and 2013. Sixty-four (53%) studies focused on dental caries prevention or treatment. Median appraisal scores calculated for full and partial EE studies were 11 and 9 out of 13, respectively. Quality assessment scores showed that the quality of partial EE studies published after 2000 significantly improved ( P = 0.02) compared to those published before 2000. Significant quality improvement was not found in full EE studies. Common methodological limitations were identified: absence of sensitivity analysis, discounting, and insufficient information on how costs and outcomes were measured and valued. EE studies in dentistry increased over the last 40 y in both quantity and quality, but a number of publications failed to satisfy some components of standard EE research methods, such as sensitivity analysis and discounting.